2007
DOI: 10.1093/jjco/hym041
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Affecting the Therapeutic Decision-making and Postoperative Mood States in Japanese Breast Cancer Patients who underwent Various Types of Surgery: Body Image and Sexuality

Abstract: This study suggests the importance of discussing body image and sexuality that has tended to be disregarded in therapeutic decision-making situations in breast cancer patients in Japan. Self-efficacy is a crucial variable for improving mood after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 12 publications
0
39
0
6
Order By: Relevance
“…Six studies included immediate reconstruction only,39, 41, 43, 4547 and three included delayed reconstruction only31, 44, 48. Most studies included both autologous and implant reconstruction or did not specify the type.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies included immediate reconstruction only,39, 41, 43, 4547 and three included delayed reconstruction only31, 44, 48. Most studies included both autologous and implant reconstruction or did not specify the type.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with breast cancer go through severe emotional problems that may be related to their socioeconomic situation, psychological make-up and coping abilities, the medical parameters of the disease, the type of operation they undergo (mastectomy or lumpectomy), other forms of adjuvant treatment (chemotherapy, hormonal therapy or radiotherapy), the side effects of the treatment, and the availability of emotional and financial support (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Adachi et al, found that patients having immediate breast reconstruction valued appearance and attractiveness to their partner more significantly than patients undergoing mastectomy alone or BCT (Adachi, Ueno, Fujioka, Fujitomi, & Ueo, 2007). Other studies have found associations between appearance investment, depression, and quality of life outcomes for breast cancer survivors irrespective of type of treatment (Moreira & Canavarro, 2010, 2012).…”
mentioning
confidence: 99%